DATA INFORMATION SYSTEM FOR TODDLERS AND PREGNANT WOMEN BASED ON ANDROID FOR HELPING EARLY HEALTH DISORDERS FOR TODDLERS AND PREGNANT WOMEN IN THE VILLAGE - Widianto Widianto; Riski Elivia Zelinda; Muhamad Muslihudin; Siska Decahyati (International Journal of Artificial Intelligence and Robotic Technology, 2021)
Data collection for toddlers and pregnant women using an Android-based application can help in the early handling of health problems, especially for toddlers and pregnant women. Early detection and treatment of health problems for toddlers and pregnant women is important to minimize the occurrence of errors in data collection and handling. Dependence on the presence of a village midwife is very high, especially for toddlers and pregnant women. One of them is a problem which occurs in the information system for data collection for toddlers and pregnant women which is still manual in inputting the data, so it is not efficient and has to input data for toddlers and pregnant women one by one and this is very time-consuming. Based on this, the researcher provides a solution to the village apparatus so that the information system is more adequate by developing an android-based application for data collection information for toddlers and pregnant women. This data collection research uses the System Development Life Cycle (SDLC) method so that the results can be more accurate. The researcher has developed an easy system for users to search for data on toddlers and pregnant women so that it is easier without having to search one by one, and users can also delete or add data easily.